Acetylsalicylic Acid (ASA) allergy in the context of NSAIDs: navigating from an immune perspective - Barrantes-Alvarado, Reychell (2024)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are used worldwide to treat pain and inflammation; however, they can trigger various types of drug hypersensitivity reactions in all age groups. A significant number of hypersensitivity reactions to NSAIDs are due to immunological mechanisms. In order to provide a basis for better understanding and medical management of acetylsalicylic acid (ASA) allergy in the context of nonsteroidal anti-inflammatory drugs (NSAIDs), this article aims to review the main aspects regarding the causes, immunologic mechanism, symptoms, diagnosis, and treatment options related to this allergy. NSAIDs are classified according to their chemical structure and their selectivity to inhibit COX enzymes. The advantages of COX-2 selective NSAIDs in minimizing gastrointestinal side effects are highlighted, and ASA is highlighted as a commonly prescribed drug because of its multifunctional activity, including prevention of stroke and myocardial infarction.